Fichas narrativas de personajes para desarrollar la comprensión de textos narrativos escritos en los alumnos 4° grado de educación primaria de la I.E. N° 10029 - Davila Baca, David Antonio (2021)
The present work of professional sufficiency entitled “narrative sheet of characters” has been used to develop the understanding of written narrative texts. The general objective of the pedagogical proposal was: To improve the comprehension of narrative texts written with the application of the strategy, narrative sheet of characters, in students of the 4th grade of primary education of the I.E. N ° 10029. The methodology of professional sufficiency work has been to promote real, authentic and useful communicative experiences related to their context, where children are able to read with satisfaction, feel identified with reading and motivated to understand texts from their local context, understanding and discovering in the text the characteristics and qualities of the characters to draw and describe them, expressing their artistic creativity and language skills. All this work will contribute to develop comprehension skills for written narrative texts. The strategy (character narrative cards) was applied in 20 students of the 4th grade of the I.E. N ° 10029 and it consisted of compiling comics and stories from the local context; these texts were read by the students following a pedagogical and didactic process; after understanding the text, each of the students had to elaborate their character sheet that was evaluated by a checklist. The results obtained during the process of applying the didactic strategies (character narrative sheets) led us to affirm that the strategy significantly favors the development of the comprehension of written texts in 4th grade primary school students from I.E. No. 10029.